Inhibitor Enzim sebagai Terapi Targeted dalam Kanker: Tinjauan Kimia Medisinal - Muhammad Rahmat Darmawan; Saeful Amin (Universitas Pahlawan Tuanku Tambusai, 2025)
Cancer is a leading cause of global mortality, necessitating more effective and selective therapies. This study aims to evaluate the potential of enzyme inhibitors, particularly kinase inhibitors, as targeted therapy in cancer treatment. The methodology employed is an in vitro experimental design, testing against cancer cell lines MCF-7, A549, and HT-29. The results indicate that kinase inhibitors significantly reduce cancer cell viability with lower IC50 values compared to protease inhibitors. These findings underscore the greater potential of kinase inhibitors as a safer and more effective alternative cancer therapy. In conclusion, this research provides new insights into the use of enzyme inhibitors in cancer therapy and opens avenues for the development of new compounds that could enhance clinical outcomes in the future. It is recommended to explore the combination of enzyme inhibitors with other therapies and conduct clinical studies to evaluate their effectiveness in a broader patient population.